Mongilalo and the Prophet’s Hadith: Reception in Gorontalo Marriage Rituals and Its Implications for Family Resilience - Muhammad Rifian Panigoro; Roshimah Shamsuddin; Hikmawati Sultani; Ananda Saliko (Mozaic : Islam Nusantara, 2026)
This study examines the crisis of family resilience in the modern era, marked by increasing divorce rates in Indonesia. In response, it aims to reconstruct the mongilalo tradition in Gorontalo as a preventive strategy grounded in local wisdom. Mongilalo refers to a family-based evaluation of a prospective spouse to assess character readiness, ethics, and social background in order to prevent the formation of dysfunctional families. This study employs a qualitative-analytical approach. The findings show that mongilalo functions as a preventive social mechanism in strengthening family resilience through discreet assessment of prospective partners. This practice demonstrates theological coherence with the Prophet’s hadith, particularly those narrated by An-Nasa'i and At-Tirmidhi, which encourage knowing a prospective spouse to ensure marital harmony and continuity. From a juridical-philosophical perspective, mongilalo can be categorized as a valid custom that does not contradict Islamic law, as it promotes public benefit and aligns with Gorontalo philosophical values. The study concludes that mongilalo represents a relevant form of local wisdom consistent with the Prophetic Sunnah and has the potential to strengthen family resilience amid modern challenges. Therefore, integrating local wisdom and hadith should be further developed through interdisciplinary approaches to enrich culturally grounded models of family resilience.